The Relationship between Students’ Perceptions of Discipline and Student-Teachers Violence in Coping with Academic Strains - Kaumpungan, Pisonya; Ni Made Martini Puteri (12th International Scholars Conference 2025, 2026)
This study analyzes the relationship between students' perceptions of teachers' punitive and restorative disciplinary approaches and their tendency to respond to school tensions with violence. Using a mixed methods approach, integrating quantitative and qualitative data, data were collected from 96 students aged 12-17 through a quantitative survey and fromteachers and parents through interviews and open-ended questionnaires. The results of multiple regression analysis indicate that punitive and restorative disciplinary approaches are significantly related to students' tendency to chooseviolence as coping strategy in dealing with strains. Several social bonding aspects also are significantly related to students'tendency to choose violence. These findings emphasize the importance of school-family collaboration in building fair and consistent discipline